Administración y Operación de Redes de datos - DECDFI (My University, 1998)
As the name implies, an exceptional condition. An exception is something that is out of the ordinay. Most often, exceptions are used as a way to report error conditions. Exceptions can be used as a means of indicating other situations as well. This chapter concentrates primaliry on exceptions as an error handling mechanism.
Keywords: java; terminology; managing; services; eventos